A Cross-Sectional Study on Chinese Geriatricians’ Knowledge, Attitudes, and Practices Regarding Oral Anticoagulants for Atrial Fibrillation Patients - Chen Y; Liang Y; Qin M; Liu Q (Journal of Multidisciplinary Healthcare)
Yiwen Chen, Yinghui Liang, Mingzhao Qin, Qian Liu Department of Geriatrics, Beijing Tongren Hospital, Capital Medical University, Beijing, 100730, People’s Republic of ChinaCorrespondence: Mingzhao Qin, Department of Geriatrics, Beijing Tongren Hospital, Capital Medical University, Beijing, 100730, People’s Republic of China, Email 13683371884@163.comPurpose: Anticoagulants are regularly used to manage atrial fibrillation, but the decision-making styles of geriatricians regarding oral anticoagulants in atrial fibrillation in China are poorly known. This study aimed to evaluate the knowledge, attitudes, and practices of geriatricians regarding the use of oral anticoagulants in elderly patients with non-valvular atrial fibrillation.Patients and Methods: In late 2023, 210 geriatricians participated in an online survey assessing their knowledge, attitudes, and practices related to anticoagulation therapy. The survey included questions designed to gauge understanding and application of guidelines in treating elderly patients with atrial fibrillation.Results: The findings revealed an average knowledge score of 9.84 out of 14 among participants, indicating a need for improvement. Attitude and practice scores were higher, averaging 45.76 and 44.48 out of 55, respectively. Notably, the multivariate analysis showed that geriatricians aged ≤ 40 years, those practicing outside Beijing, and those in non-public tertiary hospitals demonstrated lower levels of knowledge. Additionally, there was a positive correlation between higher knowledge and favorable attitudes toward anticoagulation, while more experience (5– 10 years) and better knowledge were associated with proactive clinical practices.Conclusion: The study underscores the necessity to enhance education and training for geriatricians, focusing on younger professionals and those in particular regions and hospital types. By improving knowledge and awareness, the management of anticoagulation therapy for elderly patients with atrial fibrillation can be optimized, ultimately benefiting patient care and outcomes within this vulnerable population.Keywords: attitude, knowledge, practice, atrial fibrillation, anticoagulants